Conformational and electronic variability of N,N’,O-ligand documented on its coordination to main group halides - Milasheuskaya, Yaraslava; Růžičková, Zdeňka; Růžička, Aleš; Podzimek, Štěpán; Jambor, Roman; Novák, Miroslav (Royal Society of Chemistry, 2025)
The coordination chemistry of non-symmetric ligand L (L = 2-(C(Me)vN(C6H3-2,6-iPr2))-6-((iPrO)2PvO) C5H3N) is with a focus on its ability to adapt its denticity to accommodate different main-group elements within a potentially tridentate ‘pocket’ defined by its phosphonate PvO and imine CvN groups together with the pyridine-nitrogen atom. For this purpose, chlorides of groups 13, 14, and 16 were selected, namely InCl3, GeCl2,Ph3SnCl, Ph2SnCl2, SeCl4 and TeCl4. The reaction of L with GeCl2 and InCl3 produced [GeCl(L)][GeCl3] (2) and [InCl3(L)] (5), respectively. In both compounds, L coordinates to the central metal through all its donor atoms with a κ3-N,N,O-coordination mode. On the contrary, L coordinates Ph3SnCl and Ph2SnCl2 through only the phosphonate PvO group, resulting in κ1-O-coordinated [Ph3SnCl(L)] (3) and [Ph2SnCl2(L)] (4). The diverse chelating ability of L was found in the reaction with TeCl4 and SeCl4 yielding 2-(C(CHvSeCl2)vN(Dipp))-6-((iPrO)2PvO)C5H3N(6) and 2-(C(CH2TeCl3)vN (Dipp))-6-((iPrO)2PvO)C5H3N(7) as a result of a C–H bond activation in the Me group of the C(Me)vN fragment. Due to the presence of the M–Cl bond, all compounds 2–7 were subjected to reduction reactions with the aim of synthesising low-valent derivatives. However, only the reduction of 2 with K or KC8 led to the successful isolation of a product, [Ge(L)] (8). Finally, theoretical studies were carried out to better understand the formation of 6 and 7 as well as the electronic properties of 8.